Wpływ procesów demograficznych na prawo wyborcze - Kuchciak, Anna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2018)
The aim of this article is a brief indication of demographic changes on the electoral law.Special attention is paid to the ageing of society, because the progressive character of thisprocess. The article especially emphasises – as prescribed by the Election Code dated 5thJanuary 2011 – solutions to help older people to participate in elections which includealternative voting procedures or electoral wards in welfare homes. For reference purposes, theimpact of migration movements on electoral regulations was presented
Keywords: prawo wyborcze; procesy demograficzne; osoby starsze; alternatywne sposoby głosowania; odrębne obwody głosowania